PENERAPAN UNSUR TINDAK PIDANA PENCURIAN DENGAN KEKERASAN YANG MENGAKIBATKAN HILANGNYA NYAWA ORANG PADA SATUAN RESERSE KRIMINAL KEPOLISIAN RESOR DHARMASRAYA - Lazuardi Lazuardi (UNES Journal of Swara Justisia, 2018)
Crime of theft by violence resulting in loss of life is regulated in Article 365 of theCriminal Code, so to be able to qualify acts that can be categorized as criminal acts, theinvestigator must pay attention to important and meticulous elements so that they canfulfill the criminal elements . At the investigation of the crime of theft with violence whichresulted in the loss of the lives of two members of the West Sumatra Regional PoliceMobile Brigade, Satreskrim Dharmasraya District Police conducted an investigation andapplied elements of Article 365 of the Criminal Code based on the construction of factsand construction of juridism so that the case files were declared complete and couldproceed to the narrative process .